Right to be Free from Degradation of the Environment in Sri Lanka: A Review of the Chunnakam Power Station Case - Amarasinghe, Kusal (Centre for Environmental Law and Policy (CELP), 2022)
Ravindra Gunawardena Kariyawasam Vs. Central Environment Authority and Others (Chunnakam Power Station Case) is a landmark judgment in Sri Lankan judicial history, that defined the ‘Right to be Free from Degradation of the Environment’ as a Fundamental Right. This judgment emphasised the government's duty to protect nature and conserve its riches as a national trust. Accordingly, the Chunnakam case is one of the significant judgments which underscored the ‘Public Trust Doctrine’ in Sri Lankan judicial history. Furthermore, in justifying this decision, the Supreme Court has adopted the ‘Precautionary Principle’, the ‘Polluter Pays Principle’, and the ‘Principles of Sustainable Development’.
Keywords: Fundamental Rights; Polluter Pays Principle; Public Interest Litigation; Public Trust Doctrine